Low input cattle production systems in tropical Africa: An analysis of actual and potential cow-calf productivity - Leeuw, P.N. de; Thorpe, W.R. (South African Society of Animal Science, 1996)
The biological productivity of cow-calf units in low-input production systems in tropical Africa is reviewed. Four production systems (pastoralists agropastoralists, crop-livestock farmers and smallholder farmers) are identified. Fifty-five data sets from monitoring and systems research conducted by ILCA and from other secondary sources are analysed to detect interactions between performance variables including calving rate, cow and calf mortality, milk offtake and calf growth, and relate these to factors of environment, mangement and producer goals. Through equating 1 kg of calf weight to 9 kg of milk offtake, the index kg liveweight/100 kg cow/yr is used to compare systems that vary in production goals and breeds. In low-input traditional systems cow productivity is constrained by disease and seasonal shortages of breed and water, cows produce at sub-optimal, level. To access this depression the indices from traditional systems are compared with those of indigenous cows raised in ranches and research stations. Zebus and Sanga in the semi-arid and subhumid zone produced between 15 and 25 kg/100 kg cow/yr, the proportions of low and high-yielding herds being similar. Trypanotorant cows in the sub-humid zone were relatively high-yielding (up to 30 kg) due to high extraction rates, suggesting that increased milk offtake may enchance overlal productivity. The majority of indigenous cows in ranches and research stations produced a weaned calf weight of 33-38 kg/100 kg cow or on average 75 percent more than cows in traditional systems. Further analyses are required to substantiate that high milk offtake increases overall productivity, at least i the favourable environment of the subhumid zone. Price ratios between milk and liveweight averaged 1:3, explaining why milk offtake for sale has received high priority in many traditional production systems.